Salmonella enhances osteogenic differentiation in adipose-derived mesenchymal stem cells - Mohamad-Fauzi, Nuradilla; Shaw, Claire; Foutouhi, Soraya H.; Hess, Matthias; Kong, Nguyet; Kol, Amir; Storey, Dylan Bobby; Desai, Prerak T.; Shah, Jigna; Borjesson, Dori; Murray, James D.; Weimer, Bart C. (Frontiers in Cell and Developmental Biology, 2023)
The potential of mesenchymal stem cells (MSCs) for tissue repair and regeneration has garnered great attention. While MSCs are likely to interact with microbes at sites of tissue damage and inflammation, like in the gastrointestinal system, the consequences of pathogenic association on MSC activities have yet to be elucidated. This study investigated the effects of pathogenic interaction on MSC trilineage differentiation paths and mechanisms using model intracellular pathogen Salmonella enterica ssp enterica serotype Typhimurium. The examination of key markers of differentiation, apoptosis, and immunomodulation demonstrated that Salmonella altered osteogenic and chondrogenic differentiation pathways in human and goat adipose-derived MSCs. Anti-apoptotic and pro-proliferative responses were also significantly upregulated (P < 0.05) in MSCs during Salmonella challenge. These results together indicate that Salmonella, and potentially other pathogenic bacteria, can induce pathways that influence both apoptotic response and functional differentiation trajectories in MSCs, highlighting that microbes have a potentially significant role as influencers of MSC physiology and immune activity.